Connectivity restoration in delay–tolerant sensor networks using game theory. (14th November 2012) - Senturk, Izzet; Yilmaz, Sabri; Akkaya, Kemal
Due to limited resources and harsh environments, partitioning can be inevitable in wireless sensor networks (WSNs). To re–establish network connectivity, healthy mobile sensor nodes can be repositioned in an on–demand basis. However, the nodes are equipped with limited batteries and their movement requires excessive energy consumption. In this paper, we address the problem of minimising the movement cost when re–establishing network connectivity in delay tolerant WSNs by presenting a distributed heuristic approach based on Game Theory. Compared to centralised heuristics which assume complete knowledge of the network and failures, this approach is self–healing that can work with uncertain network/failure information. Under limited knowledge on partitions and failure locations, Game Theory is used to facilitate decision making on the selection of the nodes to be moved and their movement directions. Extensive simulations have revealed the efficiency of the proposed approach in terms of movement distance and network coverage.